Penghilangan Hak Kewarganegaraan Bagi Eks ISIS - samsul arifin (Widya Yuridika, 2020)
Southeast Asia is one of the objects of ISIS ideology, especially in Indonesia and Malaysia, where the majority of the population is Muslim. The existence of a common sense of fate and the belief that there is no system of state order and good governance except the Khilafah system, this encourages them to join in. Behind the news of the death of the leader of the group raises the question of how the fate of Indonesian citizens who are incorporated in it. The statement from President Jokowi that he would not repatriate them, this got the same response from the public who thought that the former ISIS group if repatriated to Indonesia would become terrorists. This research attempts to analyze the legal impact on those who join ISIS, what policies are taken by the government, whether they will lose citizenship, and how positive laws govern them. The method used in this research is the statute approach. This approach moves from positive laws both national and international, vertical and horizontal. The purpose of this study is to determine the legal impact and clarity of citizenship rights for those who join ISIS.